Stability indicating methods for selective determination of Oxetacaine in the presence of its degradation products - Eman S. Elzanfaly; Enas A. Amer; Sara A. Galal; Hala E. Zaazaa (Faculty of Pharmacy, Cairo University, 2018)
Two methods, HPLC and TLC were presented for the determination of Oxetacaine (OXT) in the existence of its different degradation products. HPLC method was based on the separation of OXT from its degradation products using reversed phase C18 column at room temperature and isocratic elution with mobile phase mixture of acetonitrile: 5 mM sodium dihydrogen orthophosphate dihydrate, pH was adjusted to 2.4 with orthophosphoric acid (50:50 v/v). Quantitation was based on peak area at 210 nm. The second TLC-densitometric method relies on the separation and quantitation of OXT from its degradation products on TLC silica gel 60 F254 plates, using 2-propanol: triethylamine (10:0.5 v/v) as a developing system and densitometric measurement of the developed bands at 210 nm. Validation of the proposed methods was performed according to the ICH guidelines and applied to evaluate the stability of OXT under different stress conditions. Keywords: Oxetacaine, RP-HPLC method, TLC-densitometric method, Stability indicating